Early Onset Breast Cancer in a Registry‐based Sample of African‐American Women: BRCA Mutation Prevalence, and Other Personal and System‐level Clinical Characteristics. Issue 2 (16th January 2013) - Pal, Tuya; Bonner, Devon; Kim, Jongphil; Monteiro, Alvaro N.A.; Kessler, Lisa; Royer, Robert; Narod, Steven A.; Vadaparampil, Susan T.
Abstract Young Black women are disproportionately afflicted with breast cancer, a proportion of which may be due to BRCA1 and BRCA2 (BRCA) gene mutations. In a sample of Black women with early onset breast cancer, we evaluated BRCA mutations and explored personal and system‐level clinical characteristics. Black women diagnosed with invasive breast cancer (age ≤50) were recruited through the state cancer registry. Participants completed a questionnaire, genetic counseling and BRCA testing. Of the 48 women who consented to study participation, 46 provided a usable biologic specimen for BRCA testing. The overall prevalence of BRCA mutations and variants of uncertain significance (VUS) in participants was 6.5% and 34.8%, respectively. Of these, only 14 were referred for genetic counseling prior to study enrollment. Overall, those participants who chose to undergo bilateral mastectomy had a higher number of relatives with breast and ovarian cancer (p = 0.024) and a higher household income (p = 0.009). BRCA mutation prevalence and the high prevalence of VUS in participants are consistent with prior studies. Furthermore, clinical factors such as family history and financial means may influence type of surgery recommended and chosen, at both the provider and patient level, respectively. Finally, the limited number of patients referred for genetic counseling prior to surgical treatment for breast cancer may represent a missed clinical opportunity to inform surgical decisions.